2006
DOI: 10.1590/s1806-83242006000300002
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in the oral mucosa of patients submitted to allogeneic haematopoietic stem cell transplantation

Abstract: ABSTRACT:This study was designed to investigate the impact of haematopoietic stem cell transplantation (HSCT) on Helicobacter pylori colonization of the oral mucosa by nested polymerase chain reaction (nested-PCR). Forty six consecutive patients submitted to HSCT and 46 healthy volunteers were included in the study. Oral swabs were taken from the oral mucosa of the patients and control group. The medical records of the patients were reviewed and the following information was retrieved: gender and age of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Although in the paper by Correia-Silva et al, 38 no relationship between HP infection and the development of GvHD was observed in 46 patients who received an allogeneic transplant, our group reported in a retrospective study 15 with 198 patients that HP infection had a negative modulating effect on the development of acute GvHD (RR = 0.60 (95% CI: 0.46-0.79) P = 0.001) and chronic GvHD (RR = 0.75; (95% CI: 0.61-0.92) P = 0.016). Furthermore, the presence of HP was inversely correlated with the histological severity of GvHD (P = 0.003).…”
Section: Discussionmentioning
confidence: 94%
“…Although in the paper by Correia-Silva et al, 38 no relationship between HP infection and the development of GvHD was observed in 46 patients who received an allogeneic transplant, our group reported in a retrospective study 15 with 198 patients that HP infection had a negative modulating effect on the development of acute GvHD (RR = 0.60 (95% CI: 0.46-0.79) P = 0.001) and chronic GvHD (RR = 0.75; (95% CI: 0.61-0.92) P = 0.016). Furthermore, the presence of HP was inversely correlated with the histological severity of GvHD (P = 0.003).…”
Section: Discussionmentioning
confidence: 94%
“…These findings suggest that these species are not possible endodontic pathogens and that the necrotic root canal does not serve as a reservoir for these human pathogens in healthy patients [37] . In another study by Correia-Silva Jde et al [38] , many H. pylori-positive results were found in the oral mucosa of 46 haematopoietic stem cell transplantation (HSCT) patients. The authors report that their findings may be due to the patients' poor oral hygiene during the transplantation and/or immunosuppression procedures involved in HSCT therapy [38] .…”
Section: Tonsillar Tissuesmentioning
confidence: 97%
“…In another study by Correia-Silva Jde et al [38] , many H. pylori-positive results were found in the oral mucosa of 46 haematopoietic stem cell transplantation (HSCT) patients. The authors report that their findings may be due to the patients' poor oral hygiene during the transplantation and/or immunosuppression procedures involved in HSCT therapy [38] . Other authors note that, because "the oral cavity is a frequent site of local infections and an important port of entry for systemic infections in HSCT recipients..., the presence of H. pylori in the oral cavity may be a risk factor for infection or reinfection of the stomach of these patients" [9,38] .…”
Section: Tonsillar Tissuesmentioning
confidence: 97%
See 1 more Smart Citation